Factors that influence consumer purchasing behaviour towards green product: a case on cocoa / Mohamad Saifullah Md Sam - Md Sam, Mohamad Saifullah (Faculty of Plantation and Agrotechnology, 2016)
Cocoa is one of major crop in Malaysia after oil palm, rubber and paddy. In 2014, the total cultivated by region and sector is 16,070 ha. The land cultivated by this species has been reduced in large amount of hectare. Cocoa industry of import and export show the good development in cocoa processing from raw material into product form. However, development and marketing of cocoa green product still lack and need improvement. Therefore, survey study has been developed to find the factors that influence consumer to purchase green product. Merlimau is the place for survey purpose. Green product is product that has been produced without affecting the environmental surrounding. The study wants to investigate the consumer purchasing behaviour by explaining the relation of four factors; environmental concern, health, social influence and price. The primary data need to be collected from respondents by using self-administered survey. All data from respondents will be analyzed by descriptive analysis, reliability analysis, correlation analysis and regression analysis to achieve the objectives in this study. The result shows that price is the most factor influence consumer purchasing behaviour. It is hope that government and other agencies take the action in improvement of green product especially on cocoa.